2021
DOI: 10.3390/cancers13225658
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell Sequencing: Biological Insight and Potential Clinical Implications in Pediatric Leukemia

Abstract: Single-cell sequencing (SCS) provides high-resolution insight into the genomic, epigenomic, and transcriptomic landscape of oncohematological malignancies including pediatric leukemia, the most common type of childhood cancer. Besides broadening our biological understanding of cellular heterogeneity, sub-clonal architecture, and regulatory network of tumor cell populations, SCS can offer clinically relevant, detailed characterization of distinct compartments affected by leukemia and identify therapeutically ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 161 publications
0
3
0
Order By: Relevance
“…Single cell sequencing could be used to identify the gene expression and genetic variation in response to the epigenetic modifications and environmental changes 33 . Meanwhile, single cell sequencing could provide new promising strategies for cancer diagnosis, classification, targeted therapy and prognosis prediction 34–36 . In the present study, the heatmap from CancerSEA showed the different correlation between CSF3R expression and multiple functional states in different cancers, such as DNA repair, invasion, cell cycle and inflammation, etc.…”
Section: Discussionmentioning
confidence: 61%
“…Single cell sequencing could be used to identify the gene expression and genetic variation in response to the epigenetic modifications and environmental changes 33 . Meanwhile, single cell sequencing could provide new promising strategies for cancer diagnosis, classification, targeted therapy and prognosis prediction 34–36 . In the present study, the heatmap from CancerSEA showed the different correlation between CSF3R expression and multiple functional states in different cancers, such as DNA repair, invasion, cell cycle and inflammation, etc.…”
Section: Discussionmentioning
confidence: 61%
“… 21 Single-cell sequencing could provide new promising strategies for cancer diagnosis, targeted therapy, and prognosis prediction. 22 24 We used scRNA-seq to investigate the role of S100s in the immune microenvironment. By completing the hepatocyte atlas and KEGG analysis of each subpopulation, we found that the T-cell subpopulation was enriched for the RAGE receptor signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Given its importance in infant AML, murine and human model systems, combined with single-cell omic assays [ 207 , 208 , 209 ], have been developed to examine the effects of the KMT2A/MLLT3 fusion gene on AML development [ 210 ]. These include the recent development of a transplantable human KMT2A/MLLT3 AML xenograft model, using human UCB CD34 + HSPCs and CRISPR/Cas9 genome editing technologies, which also reported that the developmental age and the genetic background of the human CD34+ HSPCs, as well as the microenvironmental niche in surrogate murine models of hematopoiesis influenced AML progression [ 211 ].…”
Section: Pediatric Aml and Juvenile Myelomonocytic Leukemia (Jmml)mentioning
confidence: 99%